Application of Polysaccharide Based Composite Film Wax Coating for Shelf Life Extension of Guava (var. Bangkok Giant) - Wijewardane , R M N A (Journal of Postharvest Technology, 2024)
The application of wax coating helps to extend the shelf life of picked guava  by minimizing the weight loss due to natural migration process of moisture  and gases. The present investigation relates to find out the applicability of  different concentrations of edible coating (wax) for shelf life extension of  guava, which include palm oil (3%), glycerol (30%), Sorbitan monooleate  (tween 80) (2%) and guar gum (2%). The medium size fruits were harvested at  correct maturity (green to yellow) and only disease and damage fruits were  selected. The treatment solution was prepared by mixing wax formula with  distilled water in 1:1 (T1) and 1:2 (T2) ratios and (T3) kept as control without  any treatment. The fruits were analysed for physiological weight loss, fruit  firmness, titratable acidity, pectin content, pH, total soluble solid content and  rate of respiration for 09 days storage. The consumer acceptability was  evaluated by 30-panellist using 5 point hedonic scale. Among the treatments  tested, wax solution mixed with water in 1:1 ratio (T1) showed significantly  higher performances (p < 0.05) compared to the other treatments tested. The  selected treatment appeared to extend the shelf life of guava up to 09 days  under ambient condition (29-32°C and 65%- 70% RH) with appreciable  retention of all quality parameters tested.
Keywords: Edible coating; Guava; Shelf-life; Storage